Penjadwalan Sidang Tugas Akhir Prodi Ilmu Komputasi Universitas Telkom Menggunakan Metode Algoritma Genetika Adaptif Dan Fuzzy Relation - Oki Virgiawan Pramudita; Fhira Nhita; Annisa Aditsania (eProceedings of Engineering, 2016)
Determine a schedule that consist of many elements are complicated. One example of scheduling problems is scheduling of final project. Lot of combinations can be formed from the elemensts of this scheduling, but not all such combinations may be the solution. The scheduling of final project have requirements such lecturers teaching schedule and college student course schedule should not be conflicting to hearing schedule, examiners recommended in accordance with the topic of thesis that are tested and adviser should not be a examiners. Considering of many consideration in this scheduling, then it takes the optimal and efficient method so it can resolve the complexity of this scheduling. Fuzzy relations and genetic algorithm including methods that can be used to overcome this problem. Schedule that produced by fuzzy relation and genetic algorithm methods in this case have an average fitness of 0.9687, and for genetic algorithm methods only have an average fitness of 0.8243. Keywords: Scheduling, fuzzy relation, adaptive genetic algorithm, genetic algorithm.